Digital Inclusivity and Inequality in Language Education: Challenges and Solutions in The Digital Age - Halena Gena, Engel Bertha; Wismadewi, I Gusti Agung Galuh (LACULTOUR: Journal of Language and Cultural Tourism, 2025)
This study examined the issue of digital inclusivity and inequality in language education, particularly in the context of developing countries such as Indonesia. The problem of digital inequality was identified as multidimensional, encompassing disparities in access to infrastructure, digital skills, and equitable representation of linguistic and cultural diversity. A literature review with a descriptive qualitative approach was employed, drawing on journal articles, UNESCO reports, books, and policy documents to analyze key concepts, manifestations of inequality, and inclusive strategies. The findings indicated that digital inequality significantly affected students’ opportunities in acquiring language skills, leading to achievement gaps, exclusion of marginalized groups, and limited development of 21st-century competencies. Case studies such as Indonesia’s Rumah Belajar, Learning Equality’s Kolibri, and the Talking Book program in Africa demonstrated that inclusive, context-sensitive, and community-based approaches effectively reduced barriers by integrating low-tech solutions, multilingual content, and universal design principles. These results suggested that sustainable solutions require not only technological innovation but also policy support, cross-sector collaboration, and community participation. Therefore, inclusivity must be established as the foundation of digital language education to ensure equitable access, strengthen linguistic diversity, and promote social justice in the digital era.